Earth abundant transition metal-doped few-layered MoS2 nanosheets on CdS nanorods for ultra-efficient photocatalytic hydrogen production. Issue 39 (27th September 2017) - Hong, Sangyeob; Kumar, D. Praveen; Kim, Eun Hwa; Park, Hanbit; Gopannagari, Madhusudana; Reddy, D. Amaranatha; Kim, Tae Kyu
Abstract : This work demonstrates few-layered copper doped MoS2 nanosheets used as efficient cocatalysts on CdS nanorods to achieve ultra-efficient photocatalytic production of H2 under solar light irradiation. Abstract : The development of efficient, cost-effective, clean, and renewable ways to generate hydrogen is crucial to fulfill energy demand and relieve environmental concerns. The layered nanostructures of two-dimensional transition metal dichalcogenides (TMDs) are promising non-precious and noble-metal-free materials for use as hydrogen evolution reaction photocatalysts. The activity of TMDs mainly depends on their exposed edges because the basal planes are catalytically inactive; thus, the conversion of the basal planes to catalytically active sites is a current challenge. The doping of transition metals into the MoS2 system is a fruitful way to activate the basal plane surfaces, making them catalytically active. Herein, we report few-layered copper-doped MoS2 nanosheets decorated on CdS nanorods (FCM/CdS), which are prepared by a simple method. The photocatalytic activity of the as-synthesized FCM/CdS composites was assessed by the splitting of water to generate H2 under simulated solar light irradiation in the presence of lactic acid as a hole (h + ) scavenger. The extraordinary hydrogen production rate of 194.18 μmol h −1, a 52-fold enhancement compared to that of bare CdS, arises from the synergistic effect of the few-layered MoS2 and the metal doping, which leads to the effective separation of photogenerated charge carriers and improves the surface shuttling properties for efficient H2 production. The exceptional photocatalytic activity of FCM/CdS nanocomposites results from the improved edge sites, enhanced electronic conductivity, and the presence of new active sites. Furthermore, the observed H2 evolution rate was much higher than those for the individual few-layered MoS2 -assisted CdS (FM/CdS) photocatalysts. The H2 production rate achieved with our MoS2 -based CdS photocatalyst for water splitting under solar irradiation has been the highest observed to date. Consequently, considering the low cost and high efficiency of this system, it has enormous potential for use as a photocatalyst in various fields.